=(x-2)/(x+3)(x-3)× (x +2x-3)/(x-2) ×(x+3)/(x+1) =(x-2)/(x+3)(x-3)×(x-3)(x+1)/(x-2) ×(x+3)/(x+1) =1/(x-2) 当x=2010时 原式=1/(2010-2) =1/2008
x-2/x+3×x^2-9/x^2-4x+4计算
1个回答
相关问题
-
计算 (x²+3x+2)×(4x²+9x+3)-90
-
求(x 1)=x2x 11/2×2/3×3/4×4/5×…×9求(x 1)=x2x 11/2×2/3×3/4×4/5×…
-
3x^3 × x^4 + 2x × x^2 × x^4 - 4x^5 × (-x)^2
-
计算(1)(3x+4)(3x-4) (2)(2x+1)(2x+3) (3)(9x+4y)(9x-4y)
-
计算:(x+2/x^2-2x-x-1/x^2-4x+4)×x/4-x
-
想知道:(x 1)=x2x 11/2×2/3×3/4×4/5×…×9想知道:(x 1)=x2x 11/2×2/3×3/4
-
(2x-6)/(x²-4x+4)÷(3-x)/(x²+6x+9)×(2-x)/(x+3)
-
计算:x-2/x+3.x²-9/x²-4
-
求f(x)=x3-3x k,g(x)=(2kx-k)/(x2 2)1/2×2/3×3/4×4/5×…×9
-
计算:(-2x²y)×(3/2xy)= ,3/4x³×(-2/3x²yz)=